Queer Affirmative Practice in Africa: A Social Work Practice Model for Working with LGBTQIA+ People - Kasa, Luvo (Research in Social Sciences and Technology, 2024)
Despite the legislation put in place by the United Nations, Africa continues to grapple with issues of monosexism and heterosexism. In fact, of the 54 African countries, 33 have criminalised queer relationships, a legacy primarily attributed to colonial rule. However, social work literature has recently introduced a culturally sensitive model for working with the LGBTQIA+ community, known as Queer affirmative action. By utilising available literature and adopting an intersectional approach, which was collected and analysed through PRISMA, this paper aims to discuss the Africanising of sexuality in Africa. It argues that it is crucial to undertake a critical analysis of the colonial legacy and its impact on queer identities. Furthermore, the article posits that social work education must incorporate knowledge of the intersection of gender, sexuality, and other identity markers to form an inclusive and comprehensive approach towards practice. An affirmative philosophy to social work practice can serve as a counterweight to all punitive and discriminatory practices. Thus, in Africa, the most effective way to improve the well-being of queer individuals is to eradicate structural forms of inequality and decriminalise same-sex consensual relationships.